Amnestic MCI patients’ experiences after disclosure of their amyloid PET result in a research context - Gwendolien Vanderschaeghe (Alzheimer’s Research & Therapy, 2017)
Abstract Background Biomarkers such as amyloid imaging are increasingly used for diagnosis in the early stages of Alzheimer’s disease. Very few studies have examined this from the perspective of the patient. To date, there is only limited evidence about how patients experience and value disclosure in an early disease stage. Methods Semistructured interviews were carried out with 38 patients with amnestic mild cognitive impairment as part of an investigator-driven diagnostic trial (EudraCT, 2013-004671-12; registered on 20 June 2014) in which participants could opt to know the binary outcome (positive/negative) result of their amyloid positron emission tomography (PET) scan. Verbatim transcripts of the interviews were evaluated using qualitative content analysis and NVivo 11 software. Results Eight of 38 patients received a positive amyloid PET scan result, and the remaining 30 patients received a negative amyloid PET scan result. After disclosure of the result to the patients, we interviewed each patient twice: 2 weeks after disclosure and 6 months after disclosure. Patients had difficulties in repeating the exact words used during disclosure of their amyloid PET scan result by the neurologist; yet, they could recall the core message of the result in their own words. Some patients were confused by the terminology of an amyloid-positive/negative test result. At 6 months, two of eight patients with a positive amyloid PET scan result experienced emotional difficulties (sadness, feeling worried). Three of 30 patients with a negative amyloid PET scan result started to doubt whether they had received the correct result. Patients reported that they experienced advantages after the disclosure, such as information about their health status, the possibility of making practical arrangements, medication, enjoying life more, and a positive impact on relationships. They also reported disadvantages following disclosure, such as having emotional difficulties, feeling worried about when their symptoms might worsen, the risk of a more patronizing attitude by relatives, and the possibility of a wrong diagnosis. Conclusions This exploratory study shows that the majority of patients can accurately recall the information received during disclosure. The experienced advantages and disadvantages reported by our patients depended on the outcome of the result (positive or negative) and the interval of the conducted interview (2 weeks or 6 months after amyloid PET disclosure). Discrepancies were found between patients’ expectations according to the interview prior to amyloid PET disclosure (Vanderschaeghe et al. [Neuroethics. 2017;10:281–97]) and their actual experiences after their amyloid PET disclosure.